P-79 Distress versus harm; have we implemented changes to dnacpr documentation following the tracey judgment?. (1st March 2017) - Shayler, Stephanie; Macfarlane, Mike; Willis, Derek
Abstract : Background: Following the Tracey judgment in 2014, DNACPR decisions must now be communicated to the patient or, when this is not possible, their relatives. The only exceptions are if the patient has expressed a clear wish not to be involved or there is significant risk of causing physical or psychological harm to the patient by communicating the information. Currently there is no guidance on what constitutes 'physical or psychological harm', therefore it is subject to varying interpretation. The aim of this pilot was to investigate the communication of DNACPR decisions following the Tracey case and the interpretation of 'physical or psychological harm' by healthcare professionals. Methods: A retrospective audit of clinical notes was performed. 30 notes were analysed from 2013 (before the Tracey ruling) to determine who DNACPR decisions were communicated to and, if this information was withheld, the reasons why. 30 patient notes from 2015 (following the Tracey ruling) were analysed to obtain the same information, then a comparison was made between both years. Results: 6/30 (20%) DNACPR decisions were discussed with patients in 2013 compared to 17/30 (57%) in 2015. 4/30 (13%) decisions were discussed with families in 2013 compared to 17/30 (57%) in 2015. Reasons for not discussing DNACPR decisions in 2013: distress (79%); patient choice (13%); no reason documented (4%); anxiety (4%). Reasons for not discussing DNACPR discussions in 2015: psychological harm (39%); no reason documented (23%); patient choice (15%); patient confused (15%) patient unable to communicate (8%) Psychological harm in 2015 was described as 'extreme distress', 'anxiety', 'distress', 'extreme distress' and 'upset'. Conclusions: Communication of DNACPR decisions increased following the Tracey judgment. There was no clear consensus on what constitutes 'harm' although the term 'distress' was most commonly included in its explanation. This indicates the need for further research and guidance in this area.